A REVIEW ON FARMERS OF TELANGANA: WELFARE SCHEME CHANGING STATUS AND DEVELOPMENT - Indla Lavanya, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The situation of farmers who have been improved since the Telangana government launched the finest initiatives in Telangana state is examined in this study. Farmers have benefited from a variety of farmer-related programmes that have been created and are effectively operating. The direct and indirect initiatives assist farmers in cultivating their land. In the state of Telangana, this has never occurred before. Because Telangana is located on a rock plateau, there are no rivers flowing across the state. Some rivers run from the state's boundaries, although not from all of Telangana's districts. To address this problem and attract farmers, a variety of programmes were established from the ground level to encourage farmers to farm. The systematic review was done on literature on how traditional practises are carried out all over state with reference to the different papers published in different journals and government annual reports from the year 2015-2021. It is noteworthy that the ‘Agriculture & Allied Sectors’, which are the backbone of rural Telangana, and employ more than 55% of the population on of the state, make up the major proportion of this sector. While Telangana started out with a negative 0.7% growth rate in the ‘Agriculture & Allied Sectors’ in 2014-15, attained growth rates of 35.9% and 18.5% even during the pandemic years of 2019-20 and 2020-21. The Gross Value of Output (GVO) for paddy in 2020-21 increased 5 times its value in 2014-15, the GVO for cotton in 2020-21 increased 3 times its value in 2014-15, the GVO for ‘Meat’ in 2020-21 also increased 3 times its value in 2014-15, and the GVO for ‘Inland Fish and Prawns’, & ‘Eggs’ in 2020-21increased nearly double their respective values in 2014-15. (Des.ts,2014-2021).